PENGARUH FLUKTUASI AIR TANAH TERHADAP KANDUNGAN BAHAN KIMIA SKUNDER DAN DIVERSITAS INSEK PADA TANAMAN MELALEUCA ERICIFOLIA SM. - Watiniasih, Ni Luh (Bumi Lestari, 2010)
Fluctuation of water regimes where plant grows has been known to affect the plant chemical, nutrition compositions and plant chemical defenses, which can affect the vulnerability of plants to insect herbivores. This research aimed to compare the concentration of plant nutrition and chemical defenses of Melaleuca ercifolia grows on different water regimes, subsequently to insect herbivore attacks. The leaf total nitrogen was higher in plants growing in water fluctuated areas, therefore the insect herbivores compared to plants growing in prolong-flooded condition. Insect herbivores prefer to consume plants that are more nutritious and less affected by the plant growing conditions.